2014
DOI: 10.1111/hae.12384
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic challenges in patients with bleeding phenotype and von Willebrand exon 28 polymorphism p.D1472H

Abstract: Exon 28 polymorphism p.D1472H is associated with significantly lower von Willebrand Ristocetin cofactor activity (VWF:RCoF) to von Willebrand antigen (VWF:Ag) ratio compared to normal, but has been reported as not conferring haemorrhagic risk. The impact of this polymorphism while assessing symptomatic patients for von Willebrand disease (VWD) has not been previously analysed. We retrospectively reviewed charts of children with clinically significant bleeding and abnormal VW panel who underwent VW exon 28 anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
(14 reference statements)
1
0
0
Order By: Relevance
“…This report demonstrates that the reliance on VWF:RCo alone for diagnostic purposes can be insufficient, especially in those with the p.D1472H variant. Francis et al 9 showed similar results from a single institution study in which their retrospective analysis uncovered six patients diagnosed with type 1 VWD who had normal VWF:Ag levels and borderline low VWF:RCo, which could be explained by the presence of p.D1472H. Our data expand on this study and highlight the value of repeat testing along with using the VWF:GPIbM assay to avoid the potential pitfalls of the VWF:RCo assay.…”
Section: Ta B L E 1 Demographics Of Study Populationsupporting
confidence: 85%
“…This report demonstrates that the reliance on VWF:RCo alone for diagnostic purposes can be insufficient, especially in those with the p.D1472H variant. Francis et al 9 showed similar results from a single institution study in which their retrospective analysis uncovered six patients diagnosed with type 1 VWD who had normal VWF:Ag levels and borderline low VWF:RCo, which could be explained by the presence of p.D1472H. Our data expand on this study and highlight the value of repeat testing along with using the VWF:GPIbM assay to avoid the potential pitfalls of the VWF:RCo assay.…”
Section: Ta B L E 1 Demographics Of Study Populationsupporting
confidence: 85%